The influence of tourist experiencescape and unique perceptions on destination satisfaction and loyalty: A study of natural and cultural tourism in Indonesia - Fansuri Munawar; Rini Handayani (Journal of Enterprise and Development (JED), 2023)
Purpose — This study aims to analyze the role of the tourist experience and unique perceptions of a destination on destination satisfaction and loyalty in natural and cultural tourism models in Indonesia.Method — We employed a quantitative analysis in this study. The study's participants consisted of 100 tourists who had explored various natural and cultural tourist destinations, encompassing sites such as Tanjung Kelayang SEZ, Siak Sri Indrapura, Dieng, Borobudur Temple, Panglipuran Tourism Village, Uluwatu, Bromo Tourism, and the Heritage and Culture Museum. The data analysis method employed in this research is based on the Partial Least Square Structural Equation Model (SEM-PLS).Result — The findings of this study indicate that the variables 'tourist experiencescape' and 'unique perceptions' have a positive influence on destination satisfaction. Additionally, destination satisfaction has a significant and positive impact on destination loyalty. Furthermore, destination satisfaction mediates the relationship between the tourist experiencescape and unique perceptions of the destination on loyalty.Contribution — This research makes a significant academic contribution by addressing a noteworthy gap in the existing literature. Prior studies have not extensively explored the relationships between the tourist experiencescape, unique perceptions of destinations, destination satisfaction, and subsequent loyalty in the context of natural and cultural destinations.